Physical Interpretation of Mixing Diagrams. Issue 1 (12th January 2018) - Khain, Alexander; Pinsky, Mark; Magaritz‐Ronen, L.
Abstract: Type of mixing at cloud edges is often determined by means of mixing diagrams showing the dependence of normalized cube of the mean volume radius on the dilution level. The mixing diagrams correspond to the final equilibrium state of mixing between two air volumes. While interpreting in situ measurements, scattering diagrams are plotted in which normalized droplet concentration is used instead of dilution level. Utilization of such scattering diagrams for interpretation of in situ observations faces significant difficulties and often leads to misinterpretation of the mixing process and to uncertain conclusions concerning the mixing type. In this study we analyze the scattering diagrams obtained by means of a Lagrangian‐Eulerian model of a stratocumulus cloud. The model consists of 2, 000 interacting Largangian parcels which mix with their neighbors during their motion in the atmospheric boundary layer. In the diagram, each parcel is denoted by a point. Changes of microphysical parameters of the parcel are represented by movements of the point in the scattering diagram. The method of plotting the scattering diagrams using the model is in many aspects similar to that used in in situ measurements. It is shown that a scattering diagram shows snapshots of a transient mixing process. The location of points in the scattering diagrams reflects largely the history and the origin of air parcels. Location of points on scattering diagram characterizes intensity of entrainment, and different parameters of droplet size distributions (DSDs) like concentration, mean volume (or effective) radius, and DSD width. Plain Language Summary: In this study we critically analyze the interpretation of mixing diagrams widely used for determination of mixing type in clouds. We show principal difference between in situ measured scattering diagrams which show snapshots of a transient mixing process and mixing diagrams showing the final equilibrium state of mixing. We show that the location of points in the scattering diagrams reflects the history and the origin of air parcels. The study will help to parameterize the microphysical processes in clouds for utilization in large‐scale and climate models. Key Points: The shape of scattering diagrams reflect the snapshots of time‐dependent mixing process Scattering diagrams contain information of DSD properties but cannot be compared with the mixing diagrams to show mixing type Mixing diagrams are not suitable for analysis and determining the mixing type in clouds